Analysis on RF-DC converters for integration in radio receivers - Teixeira, Diana Lúcia de Jesus (2012)
In the current technological paradigm the electronic systems appliance is much wider than automation and control of industrial processes, and in the last years it has been directed for the satisfaction of the human needs and pleasures. As consequence of the personal usage of electronic devices it is at most interest to make them portable, thus avoiding constrains in the user mobility. However, the power supply strategy used to provide portability to the devices relies on storage elements, such as batteries or supercapacitors, whose periodical recharge can be uncomfortable or even impossible for their users. So, this project intends to avoid the manual recharge process by proposing an energy harvesting strategy capable to provide power autonomy to the device. Between many sources of energy available this work chooses to collect and convert the power of the electromagnetic waves which are crowding indoor and outdoor environments, and so it aims to study, analyse and test di erent circuits whose purpose is to convert radio-frequency signals into Direct Current (DC) power. The main focus of this circuits assessment is the power conversion e ciency and the maximum DC output voltage generation, always considering Radio Frequency (RF) signals with very low power and frequencies in the range of Ultra High Frequency (UHF). The main goal of this thesis is to make it a useful tool to be used as a support in the future project and design of Radio Frequency (RF) energy harvesting systems, as it o ers a deep evaluation in many di erent circuit topologies and its constituent elements.